Vremenski zavisna i tenziono zavisna vasoaktivnost izolovanih humanih umbilikalnih arterija - Đukanović, Đorđe; Gajić Bojić, Milica; Škrbić, Ranko (Scripta Medica, 2020)
Background/Aim: There have been different experimental conditions for in vitro studies on human umbilical arteries (HUA) in tissue bath system. This diversity was mainly reflected in variables such as stretching tension, incubation period and initial constriction challenging with potassium (KCl). The aim of the study was to establish optimal experimental conditions which will provide better responsiveness of HUA preparations, as well as to examine the impact of 24 h cold storage on viability and responsiveness of HUA to KCl and serotonin. Methods: The KCl-induced constrictions at different stretching tensions (0.5 g, 1.0 g, 2.0 g, 4.0 g), incubation times (30 min, 60 min, 120 min), and after multiple initial constriction challenging were compared. Dose response curves for serotonin were obtained under different conditions (1.0 g and 60 min vs. 2.0 g and 120 min). The influence of 24 h cold storage on KCl- and serotonin- induced vasoconstriction of HUA preparations was examined as well. Results: The strongest constrictions induced by serotonin or KCl were obtained when preparations were adjusted at 2.0 g and incubated for 120 min. The KCl-induced constrictions observed after 120 min were statistically higher (p < 0.05) when preparations were challenged three times (30 min, 60 min, 120 min), compared to those challenged only once. The preparations that were stored at 4 ⁰C for 24 h showed significantly stronger serotonin-induced constrictions (p < 0.01). The cold storage had no influence on KCl-induced constriction. Conclusion: For performing in vitro studies on HUA preparations in tissue bath, we propose stretching tension of 2.0 g, incubation period of 120 min and multiple initial constriction challenging with KCl as optimal experimental condition. We also showed that HUA preparations retained functional viability even after 24 h of cold storage.